The call: labour competencies in call centre survey services - Moench, Eric Ignacio (2024)
Introduction:  This article reconstructs the work situation in call centres that provide a telephone survey service in Argentina. Objectives: Focusing on the calls made by call centre interviewers, we ask how the work is organised, what skills are exercised in the call, and what their value is. We seek to identify and understand what kinds of job competencies enable interviewers to get different people to complete questionnaires. Method and technique: To address these issues we draw on concepts from work psychology and social studies of work (task-activity, knowledge, labour competencies, inter/intrapersonal qualities). At the empirical level, we analysed eight semi-structured interviews with call centre employees (interviewers and those who manage their work); and we analysed ten interviewer-respondent telephone interactions (auditory observation). From this material we transcribe the most significant excerpts. Results: We will argue that the interviewer's work goes beyond the simple execution of a script prior to the call. On the contrary, it implies an active attitude in tense situations, and the use of a versatile language that commands, convinces and/or calms the people contacted. In this sense, it is a combined exercise of interpersonal and intrapersonal qualities that makes it possible to control the conversation, subordinating it to the required productivity. [Continue reading in the article]